(untitled) (Plant Tissue Culture and Biotechnology, 2011)
Genetic transformation using nodal and internodal segments from three economically important potato (Solanum tuberosum L.) varieties namely, Diamant, Cardinal and Granola was conducted using an Agrobacterium tumefaciens strain LBA4404 harbouring binary plasmid pBI12 containing the GUS and nptII genes. Node and internodal segments were used for direct regeneration as well as regeneration with the intervention of callus. best responses were obtained for direct regeneration of shoots when the explants were cultured on MS supplemented with 4.0 mg/l BAP +1.0 mg/l IAA, 1.5 mg/l BAP + 0.5 mg/l IAA and 5.0 mg/l BAP +1.0 mg/l IAA in Diamant, Cardinal and Granola, respectively. In Diamant spontaneous in vitro microtuberization was obtained from these proliferated shoots. Further culturing of these in vitro grown green microtubers regenerated a large number of shoots on MS containing 4.0 mg/l BAP +1.0 mg/l IAA. By combining the best treatments, this protocol yielded an average transformation rate of 87% of treared explants. Stable expression of GUS gene was visualized in the various parts of transformed shoots through histochemical assay. Genomic DNA was isolated from transformed shoots and stable integration of the GUS and nptII genes was confirmed by PCR analysis. Key words: Potato, in vitro regeneration, transformation D.O.I. 10.3329/ptcb.v20i2.6894 Plant Tissue Cult. & Biotech. 20(2): 145-155, 2010 (December)